Distribution and morphometrics of Natalus stramineus from South America (Chiroptera, Natalidae) - Taddei, Valdir Antonio; Uieda, Wilson [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2001)
Morphometric and distributional data and some observations on the biology of Natalus stramineus Gray, 1838 collected in eastern Bolivia and in northern, northeastern, central, and southeastern Brazil are presented. All new records, combined with the records of the species from Paraguay and Mato Grosso, significantly change the known distribution of N. stramineus in South America. The specimens from northeastern Brazil (Rio Grande do Norte, Ceará, Bahia) are smaller than those found in the northern (Pará), eastern (Espírito Santo, São Paulo) and central regions of the country (Distrito Federal, Goiás, Mato Grosso do Sul). Natalus stramineus specimens from the three latter regions are about the same size, but are larger than those from Santa Cruz, Bolivia. Their size is intermediate between those of central samples and northeastern Brazil samples. The type locality of this species is discussed.
Keywords: Chiroptera; Natalus; systematics; morphometrics; distribution